Pengaruh ROM Exercise Bola Karet dengan Kekuatan Otot Pada Pasien Stroke di Ruang Interna RSUD Prof. Dr. H. Aloei Saboe Gorontalo - Nauko, Annisaturahma; Syamsuddin, Fadli; Puluhulawa, Nikmawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Stroke can cause various levels of disorders such as decreased muscle tone. Stroke treatment is physiotherapy exercises for stroke patients by providing ball gripping exercises. The aim of the research was to determine the effect of rubber ball ROM exercise on grip muscle strength in stroke patients in the Internal Room at RSUD Prof. Dr. H. Aloei Saboe Gorontalo. Methods: Pre-experimental research design with a one group pretest-posttest design approach. The samples used in this study were stroke patients who were treated in the Internal Room at Prof. Hospital. Dr. H. Aloei Saboe as many as 15 respondents, data was collected using observation sheets and tested using the parametric paired t-test statistical test. Results: The results of the study showed that muscle strength before being given the rubber ball ROM exercise was found to be an average of 2.47 with a standard deviation of 0.743 and after being given the rubber ball ROM exercise the average was 3.47 with a standard deviation of 0.743, and a p-value of 0.000 (<α 0) was obtained. .05). It was concluded that there was an influence of rubber ball ROM exercise on grip muscle strength in stroke patients in the Internal Room at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City. Conclusion: So, it is hoped that hospitals will facilitate patients by providing rubber balls so that patients can continue ROM exercise therapy using rubber balls and other stroke patients.